2021
DOI: 10.14202/vetworld.2021.1311-1318
|View full text |Cite
|
Sign up to set email alerts
|

Comparative occurrence and antibiogram of extended-spectrum β-lactamase-producing Escherichia coli among post-weaned calves and lactating cows from smallholder dairy farms in a parallel animal husbandry area

Abstract: Background and Aim: Inappropriate overuse of antimicrobials might be associated with the spreading of antimicrobial-resistant bacteria in animal-based food products. Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli have been recognized as an emerging global problem in a One Health approach. This study aimed to assess the occurrence and antimicrobial-susceptible profiles of ESBL-producing E. coli among post-weaned calves and lactating cows in a parallel animal husbandry area. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Amoxycillin [32,[35][36][37][38][39][40] 0.79 (687/869; 0.30-1.00) [28,41] 0.00 (0/37; 0.00-0.00) Amoxicillin/ Clavulanic acid [19,36,38,[42][43][44][45][46][47][48]…”
Section: β-Lactammentioning
confidence: 99%
“…Amoxycillin [32,[35][36][37][38][39][40] 0.79 (687/869; 0.30-1.00) [28,41] 0.00 (0/37; 0.00-0.00) Amoxicillin/ Clavulanic acid [19,36,38,[42][43][44][45][46][47][48]…”
Section: β-Lactammentioning
confidence: 99%
“…On the contrary, a study conducted in Thailand revealed a high degree of ESBL-EC resistance to gentamicin among cows even though the calves were susceptible to the same antibiotic. 38 The difference in the ESBL-EC sensitivity to gentamicin could be because of the routine use of aminoglycosides on cattle farms in Thailand thus creating selective pressure for the antibiotic. It is important to note that studies conducted on bacterial sensitivity to aminoglycosides within hospital settings have reported a slightly higher resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a lot of undetected community carriage and transmission of ESBL-Ec at the human-animal-environment interface [ 14 ] even though there is inadequate local evidence for this. Such insufficient evidence deters the formulation of appropriate policies, strategies, and regulations to for the control of AMR [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%